Charakterystyka geobotaniczna rzeki Pichna Szadkowicka na odcinku od źródła w Zimnej Wodzie do ujścia z terenu uroczyska Wojsławice - Woziwoda, Beata; Szczerkowska-Majchrzak, Eliza (Biuletyn Szadkowski, 2014)
The paper presents the river valley physiography and the selected hydraulic, physics and chemical parameters of the upper section of small lowland river - Pichna Szadkowicka (the Warta river catchment, Central Poland). The strong relationship between the river and river valley habitat's characteristics and the plant species and vegetation diversity was noted. Around one hundred (93) of vascular plant species was noted in total, including Listera ovata strictly protected in Poland, and partially protected: Hedera helix, Viburnum opulus, Frangula alnus and Hepatica nobilis. The high natural (botanical) and landscape values of the researched section of the Pichna Szadkowicka river with adjacent parts of Wojsławice forest complex justify additionally their protection in the network of forests reference plots and of the High Conservation Value Forests (HCFV).